PROBLEMS OF WORD RESEARCH OF THE AGRARIAN SPHERE IN UZBEK LINGUISTICS - Islamova Shahnoza (Web of Journals Publishing, 2024)
A number of problems in the field of agriculture are waiting for their solution. In particular, the colors of the soil have a number of confusions. "Sur" rang is also” Boz " color is also meaningless (synonymous) words. It can be seen from this that Boz soil (light gray), sur soil (dark gray). Blue is also not used in relation to the soil, even if it denotes gray, but it also poses various problems, as it denotes 3 different colors. The solution was for US soil scientists to develop a quantitative scale of soil color (quality) and define it by means of numbers.
Keywords: chalk, sur, Blue, Soil Scientist, soil colors, term, dictionary.